Legislation on Dental Practice in Croatia in the Second Half of the 19th Century : Zakonska regulativa dentalne prakse u Hrvatskoj u drugoj polovini 19. stoljeća - Volarić, Nikola (Array, 2021)
In the second half of the 19th century, Croatia experienced a radical change in the performance of dental practice and legislation that regulates such practice. From the old feudal system when dental practice was practised by barbers-surgeons and feldshers (Old Croatian language: vidari), it is transferred to a more modern system where dental practice becomes a part of medical sciences and its implementation requires adequate medical education. The most important factor that contributed to this was the adoption of new modern laws in 1874, and then in 1894, as well as accompanying regulations, which adequately regulated the matter of public health and dental practice.